المرجعية الأدبية في شعر محمود سامي البارودي -البنية المضمونية- البحث مستل من أطروحة الدكتوراه - فؤاد, نيان نوشيروان; محمد, ئاوات باقي (Sulaimani Journal for Humanities, 2023)
It is supposed that the reference of literature of Mahmoud Sami Al-Baroodi’s poems is the most important principle of poems, so that the going back to old Arabic literature and comprehending its meanings, content, structure and words of the source of strength and development in old Arabic literature and poem. The aim of this study is to clarify the reference of literature and its importance and styles of effect of the poet on the text of the poems, and its trial to revive the new Arabic literature movement, he is the pioneer of uprising and growing movement of Arabic literature in that historic era.